2006
DOI: 10.1002/cncr.21847
|View full text |Cite
|
Sign up to set email alerts
|

Mortality, morbidity, and cost associated with febrile neutropenia in adult cancer patients

Abstract: BACKGROUNDHospitalization for febrile neutropenia (FN) in cancer patients is associated with considerable morbidity, mortality, and cost. The study was undertaken to better define mortality, length of stay (LOS), cost, and risk factors associated with mortality and prolonged hospitalization in cancer patients with FN.METHODSThe longitudinal discharge database derived from 115 US medical centers was used to study all adult cancer patients hospitalized with FN between 1995 and 2000, comprising a total of 41,779 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
802
10
53

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 1,048 publications
(888 citation statements)
references
References 33 publications
23
802
10
53
Order By: Relevance
“…These findings support previous studies demonstrating that FN in patients who received myelosuppressive chemotherapy had an impact on early mortality. 2 It has long been acknowledged that FN represents the major dose-limiting toxicity of myelosuppressive chemotherapy and often results in prompt hospitalization for evaluation and treatment with empiric, broad-spectrum antimicrobial therapy. A systematic review of RCTs demonstrated that primary prophylaxis with a myeloid growth factor may reduce the risk of infection-related and all-cause early mortality.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These findings support previous studies demonstrating that FN in patients who received myelosuppressive chemotherapy had an impact on early mortality. 2 It has long been acknowledged that FN represents the major dose-limiting toxicity of myelosuppressive chemotherapy and often results in prompt hospitalization for evaluation and treatment with empiric, broad-spectrum antimicrobial therapy. A systematic review of RCTs demonstrated that primary prophylaxis with a myeloid growth factor may reduce the risk of infection-related and all-cause early mortality.…”
Section: Discussionmentioning
confidence: 99%
“…3,[8][9][10] FN is associated with significant morbidity and mortality, with estimates of 6.8% to 20% mortality among patients who are hospitalized for FN-related complications and with higher rates observed in patients who have major comorbidities and documented sepsis or shock. 2,[10][11][12] FN and Late Mortality Despite successful management, FN may have an equally important impact on the overall chemotherapy treatment plan, resulting in dose reductions, treatment delays, chemotherapy discontinuation, or a switch to alternative, less toxic, or potentially less effective regimens. 11,13 Myelosuppression continues to represent the major cause of reduced chemotherapy dose intensity.…”
Section: Fn and Early Mortalitymentioning
confidence: 99%
See 1 more Smart Citation
“…2 Moreover, the economical aspect of myelosuppression is very important, for example, hospitalization due to febrile neutropenia led to expenses of more than one billion US dollars during a 5-year period. 3 Thus, an approach for protection of HSCs would be extremely beneficial for the successful treatment of the tumor patient. A very interesting chemoprotective strategy is the gene therapeutic transfer of a resistance gene into HSCs.…”
Section: Introductionmentioning
confidence: 99%
“…In adult cancer patients receiving chemotherapy, febrile neutropenia (FN) is associated with considerable morbidity and in-hospital mortality of up to 10%, the risk of which increases substantially in the presence of comorbidities [1,2]. Furthermore, FN and severe neutropenia are common causes of dose delays and reductions in patients receiving chemotherapy for breast cancer.…”
Section: Introductionmentioning
confidence: 99%